Case Study on the Effect of Complementary Therapy: A Combination of ROM Therapy and Otago Exercise (ROTAGO) to Reduce the Risk of Falls in the Elderly - Nastica, Maya; Kusumawardani, Lita Heni; Iskandar, Asep (Journal of Bionursing, 2025)
ABSTRACT Background: The elderly are an advanced stage of the human life process that undergoes various anatomical and physiological changes in the body. One of them is neuromuscular changes that have an impact on decreasing muscle strength and balance disorders that result in the elderly becoming easily falling. Management to overcome the risk of falls can be carried out non-pharmacological with complementary therapy combined with ROM therapy and otago exercise (ROTAGO). Objective: This study was to determine the effect of combination therapy of ROM and otago exercise (ROTAGO) to reduce the risk of falls in the elderly. Methodology: The research method used is the case study method. This intervention was given to 3 elderly people at risk of falling, the intervention was carried out for 3 meetings with a duration of ± 40-50 minutes per day. The instrument uses TUGT. The data analysis used in this study is by using the paired t test. Study Results: The overview of the risk of falling after being given ROTAGO therapy for 1 week was that there was an average decrease in the risk of pre and post falls by 3.36 seconds. The results of the paired t test showed a significant effect of ROTAGO therapy on reducing the risk of falling in the elderly with a value of 0.009. Conclusions: There is a significant effect of combination therapy with ROM therapy and otago exercise (ROTAGO) to reduce the risk of falls in the elderly. Keywords : Elderly, Otago exercise, Fall risk, ROM therapy